Drogi afirmacji Boga (2) = The ways of the affirmation of God (2) - Zdybicka, Zofia (Zielona Góra: Uniwersytet Zielonogórski)
The author resumes her deliberations on the way or affirming God, reflecting on the history of knowledge about God in classical philosophy.
Keywords: teologia; filozofia; kultura